The status of the context in the semantic research of the commentators (Journal of the College of Basic Education, 2023)
One of the most important modern approaches to the study of meaning is the context of its various kinds.The context is advocates and supporters in the West and the East who theorized and established rules and principles in linguistics.Hadith (1).It has been proven through recent studies that the context with all its known types is one of the elementsThe task that cannot be excluded when studying meaning, because of its great importance in determiningthe meaning and directing it, because most of the words in the dictionary have more than one sign, which determines theseThe meanings are separated by the context in the text resource (2).The context theorists among the modernists, led by the English scholar (Firth), seeThat the meaning of the word is its use in the language, or the manner in which it is used, or the role in which it is used.perform it. Firth also believes that the meaning: “is revealed only through the coordination of the linguistic unit.That is, putting it in different contexts” (3). The proponents of this theory go so far as to exaggerate theEmphasis on the effect of the context in the statement of meaning, they say: “The words have no meaning on theThe release is out of place in the systems” (4).Among the advocates of this theory is the French linguist (Joseph Wenderes), who believes thatdetermines the value of the word in all cases “it is the context, as the word is found every timeThey are used in an atmosphere whose meaning is determined temporarily, and the context is the one that dictates a single value.particular to the word, despite the various meanings that it can denote, and the contextHe is also the one who purifies the word from the past connotations that memory accumulates on it.which creates an urban value for it” (5).